Legal regulation of crime reporting - Aziz, Sardar Ali (Journal of University of Human Development, 2017)
The Iraqi Legislator, in article (1-A ) of code of Criminal Procedure , has made notifying as an instrument to criminal cases , as a public right crimes ( according to the law ) it is considered to be permissible for a regular person , unless he/she knew about or seen the crime in advance is felony . It is considered to be binding for employee or assigned to public service, which knows that the crime is committed during his /her duty or due to it. However, notifying on a terrorist crimes are considered to be binding on every individual within the society without exception , article (4/3) of Anti- Terrorism Act in Kurdistan Region number (3) for the year (2006), This due to the nature of such crime and how it affects the public that lead to collective participation to combat it.